Forms of disappointment : Cuban and Angolan narrative after the Cold War - Millar, Lanie, 1979- (SUNY series in Latin American and Iberian thought and culture, 2019)
"In Forms of Disappointment, Lanie Millar traces the legacies of anti-imperial solidarity in Cuban and Angolan novels and films after 1989. Cuba's intervention in Angola's post-independence civil war from 1976 to 1991 was its longest and most engaged internationalist project and left a profound mark on the culture of both nations. After the fall of the Berlin Wall, Millar argues that Cuban and Angolan writers and filmmakers responded to this collective history and adapted to new post-socialist realities in analogous ways, developing what she characterizes as works of disappointment. Revamping and riffing on earlier texts and forms of revolutionary enthusiasm, works of disappointment lay bare the aesthetic and political fragmentation of the public sphere while continuing to register the promise of leftist political projects. Pushing past the binaries that tend to dominate histories of the Cold War and its aftermath, Millar gives priority to the perspectives of artists in the Global South, illuminating networks of anti-colonial and racial solidarity and showing how their works not only reflect shared feelings of disappointment but also call for ethical gestures of empathy and reconciliation"--